Dehalogenation and biodegradation of brominated phenols and benzoic acids under iron-reducing, sulfidogenic, and methanogenic conditions. - Monserrate, E (1997)
The anaerobic biodegradation of monobrominated phenols and benzoic acids by microorganisms enriched from marine and estuarine sediments was determined in the presence of different electron acceptors [i.e., Fe(III), SO4(2-), or HCO3-]. Under all conditions tested, the bromophenol isomers were utilized without a lengthy lag period whereas the bromobenzoate isomers were utilized only after a lag period of 23 to 64 days. 2-Bromophenol was debrominated to phenol, with the subsequent utilization of phenol under all three reducing conditions. Debromination of 3-bromophenol and 4-bromophenol was also observed under sulfidogenic and methanogenic conditions but not under iron-reducing conditions. In the bromobenzoate-degrading cultures, no intermediates were observed under any of the conditions tested. Debromination rates were higher under methanogenic conditions than under sulfate-reducing or iron-reducing conditions. The stoichiometric reduction of sulfate or Fe(III) and the utilization of bromophenols and phenol indicated that biodegradation was coupled to sulfate or iron reduction, respectively. The production of phenol as a transient intermediate demonstrates that reductive dehalogenation is the initial step in the biodegradation of bromophenols under iron- and sulfate-reducing conditions.